2016
DOI: 10.3844/ojbsci.2016.152.158
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA Fragmentation and Apoptosis Levels: A Comparison of the Swim up and the Density Gradient Centrifugation Methods for Sperm Preparation

Abstract: This study investigated the efficiency of two sperm preparation methods, namely, density gradient centrifugation and the swim-up method, in selecting spermatozoa based on the DNA fragmentation index and the apoptosis levels. Fifteen semen samples from infertile couples underwent sperm preparation in this study. The Makler ® counting chamber and Eosin Y staining were used to analyse the sperm concentration, motility and viability. The sperm chromatin dispersion assay was used to determine the sperm DNA fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
2
2
1
Order By: Relevance
“…It means too that this study confirms the result of Almeida et al [28]. In addition, Lestari SW et al also demonstrated that the sperm DNA fragmentation level was lower in the SU method compared to the DGC method, which was in line with the result of this study [29]. Furthermore, the results of this study were in agreement with the previous study that showed the lower level of caspase 3 expression as a representative of the apoptotic status in prepared sperm compared to the whole semen, even though the SU method was showed the lower level compared to the DGC method [29].…”
Section: Ca 2+-atpase Activity In Sperm From Whole Semen and Preparedsupporting
confidence: 82%
See 1 more Smart Citation
“…It means too that this study confirms the result of Almeida et al [28]. In addition, Lestari SW et al also demonstrated that the sperm DNA fragmentation level was lower in the SU method compared to the DGC method, which was in line with the result of this study [29]. Furthermore, the results of this study were in agreement with the previous study that showed the lower level of caspase 3 expression as a representative of the apoptotic status in prepared sperm compared to the whole semen, even though the SU method was showed the lower level compared to the DGC method [29].…”
Section: Ca 2+-atpase Activity In Sperm From Whole Semen and Preparedsupporting
confidence: 82%
“…In addition, Lestari SW et al also demonstrated that the sperm DNA fragmentation level was lower in the SU method compared to the DGC method, which was in line with the result of this study [29]. Furthermore, the results of this study were in agreement with the previous study that showed the lower level of caspase 3 expression as a representative of the apoptotic status in prepared sperm compared to the whole semen, even though the SU method was showed the lower level compared to the DGC method [29]. Studies have shown that the amount of caspase 3 expression of sperms in fertile and infertile men was decreased after DGC methods, related to the deficit of immature sperm with higher expression of caspase 3.…”
Section: Ca 2+-atpase Activity In Sperm From Whole Semen and Preparedsupporting
confidence: 81%
“…(Fig.2) On the contrary, in the 'moderate' and 'severe' category, the DFI of prepared sperm was lower compared to the whole semen. In contrast to the 'mild' category, this finding did not support the result by Jayaraman et al [3], but promoted the result by Lestari et al [6]. This could be explained by the existence of more sperms with DNA damage in the 'moderate' and 'severe' category of sperm sample, than the 'mild' category.…”
Section: Resultscontrasting
confidence: 56%
“…In addition, studies also reported that ALA enhances sperm ability to tolerate higher volumes of free radical attack, thus protecting the DNA integrity of the sperm [5]. Moreover, ALA also has proven in decreasing the sperm DNA fragmentation, related to the production of ROS [6].…”
Section: Introductionmentioning
confidence: 99%
“…In In addition, sperm in the semen that underwent washing before ART in IUI and IVF-ICSI programs underwent a selection process to obtain sperm with more intact DNA or less fragmented DNA than before washing, so sperm of higher quality was used for IUI and IVF-ICSI programs. 15…”
Section: Discussionmentioning
confidence: 99%